WTO trade monitoring ten years on: Lessons learned and challenges ahead - Peter Bogetoft Pedersen; Antonia Diakantoni; Carlos Pérez del Castillo; Amaliia Mkhitarian (World Trade Organization (WTO), 2018)
A decade has passed since the onset of the global financial crisis in 2008. Less than a month after the collapse of the investment bank Lehman Brothers, an internal Secretariat Task Force was established by the WTO Director-General to monitor the trade related developments associated with the global financial crisis. When G20 Leaders met in London in early 2009 they mandated the WTO, together with other international bodies, to monitor and report publicly on the G20 adherence to resisting protectionism and promoting global trade and investment. Ten years of trade monitoring later, and notwithstanding widespread anti-trade rhetoric, a protectionist backlash has not materialized. Although there have been worrying increases in the application of certain trade restrictive policy measures, the overall reality has been less alarmist. The paper will provide an introduction to the WTO trade monitoring exercise. It will show how the idea and the principles behind the current trade monitoring effort have origins that go back considerably further than the financial crisis. The paper will also provide an overview of selected trends and developments identified by the monitoring exercise since 2009. Finally, the paper will address some of the challenges facing the WTO monitoring exercise as it enters its tenth year.
Keywords: F13; F14; F61; 330; trade monitoring; protectionism; trade restrictions; trade facilitation